2010
DOI: 10.1371/journal.pone.0014263
|View full text |Cite|
|
Sign up to set email alerts
|

Common MicroRNA Signatures in Cardiac Hypertrophic and Atrophic Remodeling Induced by Changes in Hemodynamic Load

Abstract: BackgroundMechanical overload leads to cardiac hypertrophy and mechanical unloading to cardiac atrophy. Both conditions produce similar transcriptional changes including a re-expression of fetal genes, despite obvious differences in phenotype. MicroRNAs (miRNAs) are discussed as superordinate regulators of global gene networks acting mainly at the translational level. Here, we hypothesized that defined sets of miRNAs may determine the direction of cardiomyocyte plasticity responses.Methodology/Principal Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 40 publications
(66 reference statements)
2
21
0
Order By: Relevance
“…Many of the induced and repressed miRs were regulated in the same direction in fetal, hypertrophic, and failing human hearts, consistent with the known reactivation of the fetal gene program with stress (18,51). Also noted were unique subsets of miRs dysregulated with each disease state: hypertrophy, ischemic heart disease, and dilated cardiomyopathy.…”
supporting
confidence: 56%
“…Many of the induced and repressed miRs were regulated in the same direction in fetal, hypertrophic, and failing human hearts, consistent with the known reactivation of the fetal gene program with stress (18,51). Also noted were unique subsets of miRs dysregulated with each disease state: hypertrophy, ischemic heart disease, and dilated cardiomyopathy.…”
supporting
confidence: 56%
“…Based on the previous studies, it can be concluded that associations with CVDs have been shown for some of herein identified miRNAs (as is the case for miR-483-5p showing the relationship with angiogenesis 29 or miR-224 showing altered expression profile in myocardial hypertrophy). 30 Moreover, miRNA function is often associated with the effect on the course of neoplasia. Although similar association studies are also conducted for miRNAs relation to phenotype and pathophysiology of the cardiovascular system, they are far less numerous.…”
mentioning
confidence: 99%
“…Cardiac atrophy was induced in syngeneic male Lewis rats (270±5 g, n= 34, Charles River, Sulzfeld, Germany) by heterotopic abdominal heart transplantation as previously described [12,14,21,22,29,40,41,45,46]. The donor heart was harvested under deep anaesthesia (thiopental-sodium, 100 mg/kg body weight) and was transplanted into the abdominal cavity of the recipient rat under isoflurane anaesthesia (2-2.5 %).…”
Section: Animal Modelmentioning
confidence: 99%
“…The transplanted (atrophic) and the orthotopic (control) hearts of the recipient animal were removed in deep anaesthesia (thiopental-sodium, 100 mg/kg body weight) 2 weeks after transplantation. An unloading period of 2 weeks was chosen to induce a stable cardiac atrophy in accordance with previous studies [12,14,40,41] while avoiding the detrimental effects of prolonged unloading on cardiac excitation-contraction coupling and contractility [21,22,29,45]. For all experiments, the orthotopic hearts served as corresponding controls.…”
Section: Animal Modelmentioning
confidence: 99%